The Contribution of Halalan Tayyiban as an Epistemological Foundation of Sharia Economics Based on Maqasid Al-Shariah - Muhammad Syauqillah; Siswanto; Aunur Rofiq (Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Abstract Contemporary Islamic economics faces an epistemological gap between rapid innovation, digital transactions, and increasingly complex financial instruments, and the ability of classical fiqh and modern regulation to provide ethical, measurable, and maṣlaḥah-oriented operational standards. This study aims to reconstruct the contribution of halal ṭayyiban as a normative and epistemological foundation for developing maqāṣid al-sharīʿah-based Islamic economics. This research uses qualitative library research with conceptual, content analysis, and descriptive-analytical approaches to classical and contemporary literature. The findings show that halal ṭayyiban is not limited to the legality of products and transactions, but also includes commodity quality, integrity of economic actors, contractual transparency, social responsibility, and ecological sustainability. Its integration with maqāṣid al-sharīʿah strengthens the protection of religion, life, intellect, lineage, and wealth through the synergy of operational and normative dimensions from pre-contract, contract, to post-contract stages. The implication is that halal ṭayyiban can serve as a global quality benchmark, strengthen halal value chains, build consumer trust, promote welfare distribution, distinguish Islamic economics from conventional economics, and respond to contemporary moral, social, and ecological crises. Thus, Islamic economics is affirmed as a just, inclusive, sustainable, and raḥmatan lil-ʿālamīn system. Abstrak Penelitian ini bertujuan merekonstruksi konsep halal ṭayyiban sebagai landasan normatif dan epistemologis dalam pengembangan ekonomi syariah berbasis maqāṣid al-syarī‘ah. Latar belakang penelitian ini berangkat dari kebutuhan ekonomi syariah kontemporer terhadap kerangka konseptual yang tidak hanya menekankan aspek legalitas formal, tetapi juga kualitas substansial, etika, kemanfaatan, dan keberlanjutan. Penelitian ini menggunakan jenis penelitian kualitatif dalam bentuk studi kepustakaan dengan pendekatan konseptual dan analisis deskriptif untuk menelaah keterkaitan antara prinsip halal ṭayyiban dan tujuan syariat dalam sistem ekonomi modern. Hasil penelitian menunjukkan bahwa konsep halal ṭayyiban memiliki dimensi integral yang mencakup legalitas proses, kualitas komoditas, integritas perilaku, serta tanggung jawab sosial dan ekologis. Integrasi konsep ini dengan maqāṣid al-syarī‘ah memperkuat perlindungan terhadap agama, jiwa, akal, keturunan, dan harta, sehingga ekonomi syariah tidak berhenti pada kepatuhan formal, tetapi bertransformasi menjadi sistem yang berkeadilan, transparan, dan berorientasi maslahat. Secara implementatif, paradigma ini mendorong standardisasi kualitas produk, kejujuran akad, perlindungan konsumen, penguatan rantai nilai halal, distribusi kesejahteraan, dan pelestarian lingkungan. Penelitian ini menegaskan bahwa halal ṭayyiban bukan sekadar simbol religius, melainkan paradigma substantif yang mampu memperkuat daya saing ekonomi syariah, menjawab tantangan global, dan mewujudkan sistem pembangunan yang inklusif, berkelanjutan, serta berkeadaban